Cyclic deformation and damage mechanisms of 9%Cr steel under hybrid stress-strain controlled creep fatigue interaction loadings. (October 2021) - Zhang, Tianyu; Wang, Xiaowei; Ji, Yunnan; Tang, Jianqun; Jiang, Yong; Zhang, Xiancheng; Gong, Jianming
Highlights: The hybrid-controlled creep-fatigue interaction (HCFI) tests have been performed. All of the conducted HCFI tests can be divided into two regions. The failure mechanisms of the HCFI tests in different regions have been clarified. A new life prediction method based on the steady growth rate has been proposed. Abstract: The hybrid stress–strain controlled creep-fatigue interaction (HCFI) loadings at various dwell conditions were conducted on 9%Cr steel at 625 °C to investigate the deformation and damage mechanisms. Results reveal that the HCFI tests with conservative dwell conditions show complicated cyclic responses and low creep strain. The failure specimens demonstrate strong creep-fatigue interaction damage (CFID) with many branched surface cracks. With the increase in dwell stress and time, the HCFI tests show continuous softening and remarkable creep deformation. The creep-dominant damage (CDD) featured by internal creep cavities and blunt surface cracks leads to the final failure.